Putas y Discas: Sex Work Activism and Disability Justice in Argentina - Leyla Savloff (Disability Studies Quarterly, 2022)
This article examines how mutual aid efforts between sex work activists and disability activists straddled the tension between respectability politics and subversive work to invigorate feminist disability justice in Argentina. I specifically focus on a 2021 Instagram Live conversation titled "Putas y Discas" to elucidate how public debates during a pandemic and in the digital age contribute to the conceptualization of 'access intimacy,' a term introduced by disability activist Mia Mingus. I attended the event as a user taking notes and paying attention to how labor rights, disability justice, and online censorship converge in the Global South to strengthen the solidarity between sex work and disability activists, featuring digital platforms as a potential arena to uphold access intimacy. The juncture of sex work and disability activisms in Argentina informs notions of interdependency more broadly and reconfigures the relationships between vulnerability and resistance, especially in the pandemic context. "Putas y Discas" invites us to include sex as integral to health demands and recognize sexual assistance as part of a bundle of disability policies covered by healthcare. A more inclusive politics of desire can also identify the labor of sex workers as communal care and consider how the more revolutionary aspects of sex work can inform the broader politics of labor. In the form of access intimacy, sex work activism and disability activists contest the malfunctioning healthcare system that bypasses sexuality as integral health, displaying the vitality of collectives and the possibilities for digital activism.
Keywords: access intimacy; digital media; Argentina; sexual assistance; sex work activism; disability activism